2004
DOI: 10.1117/12.528976
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic imaging of blood vessels in the chorioallantoic membrane of a chicken embryo

Abstract: Photoacoustic imaging is demonstrated in imaging blood vessels of a chicken embryo. Using a weighted sumand-delay beamforming algorithm we were able to reconstruct two-and three-dimensional images of these blood vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These time-trace waves disperse through the tissue and can be seized by the detector at the tissue surface. The dispersion time determines the photoacoustic position [ 173 ]. The strength and the profile of the captured signals carry the overall spatial information about the distribution of laser absorption in the tissue [ 174 ].…”
Section: Methods To Image and Evaluate The Changes In The Vasculatmentioning
confidence: 99%
See 1 more Smart Citation
“…These time-trace waves disperse through the tissue and can be seized by the detector at the tissue surface. The dispersion time determines the photoacoustic position [ 173 ]. The strength and the profile of the captured signals carry the overall spatial information about the distribution of laser absorption in the tissue [ 174 ].…”
Section: Methods To Image and Evaluate The Changes In The Vasculatmentioning
confidence: 99%
“…A photoacoustic system was used to visualise single blood vessels in the CAM at ED 9, which revealed that the majority of vessels were sized from 200 to 500 µm in diameter, with other smaller vessels ranging from 125 to 200 µm. Meanwhile, through 3D rendering of the reconstructed dataset, the blood vessels’ structures of 3.5 mm depth became clearly visible [ 173 ]. In most cases, photoacoustic signals were acquired at flat and reflective surfaces.…”
Section: Methods To Image and Evaluate The Changes In The Vasculatmentioning
confidence: 99%